FILSAFAT ILMU DAN METODE ILMIAH EKONOMI ISLAM MENUJU KEILMUAN YANG RESPONSIF DAN BERKEADILAN - Lisana Tartila; Soraya Azzahra; Siti Nadya Alziari; Shakilla Amelyanti; Bagas Astaghina (Taksasila Edukasi Insani, 2026)
This research aims to analyze the fundamental role of the philosophy of science in building an Islamic economic system that is responsive to the dynamics of the times and adheres to the principle of justice. Amidst the failures of the conventional economic system, which often separates the moral dimension from material activities, Islamic economics presents an integrative solution that unites revelation and reason. By utilizing 25 selected academic sources from the 2021-2026 period, this study employs a qualitative-descriptive method with ontological, epistemological, and axiological approaches. The results indicate that Islamic economics as a discipline requires a solid epistemological foundation through the integration of Ushul al-Tafsir and rationalist approaches. Epistemologically, the integration of monotheistic values and empirical objectivity enables ijtihad to formulate effective policies in addressing global challenges. Axiologically, responsive economic development is realized through strengthening transparent ZISWAF instruments, implementing a green economy linked to SDGs, and adapting to digital banking transformation to achieve holistic welfare (falah) in the modern era.Keywords: Philosophy of Science, Islamic Economics, Epistemology, Digital Banking, Green Economy, Economic Responsiveness.